The Importance of Creditworthiness Evaluation in the Context of Lithuanian SME Performance Measurement - Venckevičiūtė, Gerda (Ekonomika, 2015)
The paper deals with the methodology of Lithuanian small and medium enterprises (here and further – SME) creditworthiness evaluation and part of empirical research which reveals the importance and motives of creditworthiness evaluation in the Lithuanian SME performance measurement process. The aim of this study is to analyse the importance of creditworthiness evaluation in performance measurement and its influence on stable company’s growth. The three main goals of the paper are: 1) to reveal the methodology of Lithuanian SME creditworthiness evaluation, 2) to analyse the periodicity of Lithuanian SME creditworthiness evaluation and the motives of one’s integration into the performance measurement process, and 3) to identify creditworthiness evaluation factors which correlate with stable SME growth results. Analysis of related literature, information comparison and generalization are used for the credit risk and creditworthiness evaluation methodology overview. Empirical research is performed using the survey method, for data evaluation the descriptive statistics method, as well as qualitative (systematization, classification, causal, functional and structural links) and quantitative data analysis (quantitative indicators calculation) were applied. The research results have revealed that the companies evaluating partners’ and their own creditworthiness have by 10% higher three last year revenues and the number of employees growth. The paper concludes that creditworthiness evaluation and stable company’s growth correlate and enable SMEs to pursue stable growth results while increasing competitiveness and considering confidence and trust among business partners.
Keywords: credit risk; creditworthiness; creditworthiness evaluation; SME performance measurement